Researching Regional and Rural Music Scenes: Toward a Critical Understanding of an Under-theorized Issue. Issue 4 (7th August 2020) - Bennett, Andy; Green, Ben; Cashman, David; Lewandowski, Natalie
ABSTRACT: Research on regional and rural popular music scenes focuses on a number of issues and challenges confronting such scenes. These include venues, work and employment, regional sensitivity to boom-and-bust scenarios in local heavy industries, tourism and leisure, and out-migration. To date, however, there has been very little critical examination of what precisely is meant by the terms "regional" or "rural" in relation to music scenes. This article considers some of the complex issues at play in the defining and enacting of region and a regional sense of place in the context of regional and rural popular music scenes.